2018
DOI: 10.3389/fnhum.2018.00379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cognitive Control Exertion and Motor Coordination on Task Self-Efficacy and Muscular Endurance Performance in Children

Abstract: Emerging research shows a strong connection between brain areas governing cognition and motor behavior. Indeed, research based on the Strength Model has shown that people perform worse on physical tasks following the exertion of high (compared to low) cognitive control which has been attributed to the dysregulation of neurophysiological processes within areas of the brain responsible for cognition. Yet, research investigating the negative aftereffects of high cognitive control (HCC) exertion on task performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 96 publications
1
8
0
Order By: Relevance
“…One of the most interesting ideas that emerges from the analysis of the obtained results is that a very high level of self-efficacy and confidence in one's own powers diminishes performance. This point of view is consistent with the results of recent studies ( [44,45], which show that self-efficacy negatively influences performance following the exertion of cognitive control.…”
Section: Discussionsupporting
confidence: 92%
“…One of the most interesting ideas that emerges from the analysis of the obtained results is that a very high level of self-efficacy and confidence in one's own powers diminishes performance. This point of view is consistent with the results of recent studies ( [44,45], which show that self-efficacy negatively influences performance following the exertion of cognitive control.…”
Section: Discussionsupporting
confidence: 92%
“…https://figshare.com/articles/The_effect_of_ego_depletion_or_mental_fatigue_on_subsequent_physica l_endurance_performance_A_commentary_and_meta-analysis/9255425 CWRTT Graham et al, 2018(Graham, Li, Bray, & Cairney, 2018 between groups stroop task 5 children 37 33 low handgrip task TTE (Staiano, Bosio, Piazza, Romagnoli, & Invernizzi, 2018 Alberts et al, 2007, (Alberts, Martijn, Greb, Merckelbach, & de Vries, 2007 exp 1 between groups labyrinths 10 university students 20 20 low hand grip TTE Alberts et al, 2007, (Alberts et al, 2007 exp 2 between groups labyrinths 10 university students 20 20 low hand grip TTE Ciarocco et al, 2001, (Ciarocco, Sommer, & Baumeister, 2001 Table 1 Publications details. For each trial, here are reported the trial design, the number of subjects per trial (in the case of between group design, N refers to the number of subjects in the intervention group), the type of subject population tested, the type of demanding cognitive task used and its duration (in minutes), the detail of the physical task tested and the task value attributed to the endurance task.…”
Section: Data Statementmentioning
confidence: 99%
“…The practice of taekwondo provides improvement in physical condition [ 2 , 3 ], good neuromuscular coordination and balance, harmony in movements [ 4 , 5 ] and learning of fighting skills. The development of neuromuscular coordination is a prerequisite for learning, refinement, stabilization and application of Taekwondo skills and the relative execution techniques [ 6 , 7 ]. High-level competitors in this sport are focusing on their coordination improvement, which could increase training effectiveness for their competence [ 8 ].…”
Section: Introductionmentioning
confidence: 99%